2011
DOI: 10.1161/hypertensionaha.110.165969
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Continuous Positive Airway Pressure on Prehypertension and Masked Hypertension in Men With Severe Obstructive Sleep Apnea

Abstract: Abstract-Obstructive sleep apnea and hypertension are common conditions that frequently coexist. Continuous positive airway pressure (CPAP) reduces blood pressure in patients with obstructive sleep apnea and sustained hypertension. However, the impact of CPAP on patients with obstructive sleep apnea and prehypertension and masked hypertension, conditions associated with increased cardiovascular risk, is unknown. Thirty-six male patients (age, 43Ϯ7 years; body mass index, 28.8Ϯ3.0 kg/m 2 ) with untreated severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 43 publications
4
73
1
8
Order By: Relevance
“…Some previous studies have shown that PAP therapy was associated with lower BPs in individuals with prehypertension9 or clinical hypertension,43, 44 although results were inconsistent,45, 46 likely attributable to the effects of confounding variables, such as age, severity and duration of OSA, severity of hypertension, and other factors that affect OSA severity and arterial injury as discussed in the Introduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some previous studies have shown that PAP therapy was associated with lower BPs in individuals with prehypertension9 or clinical hypertension,43, 44 although results were inconsistent,45, 46 likely attributable to the effects of confounding variables, such as age, severity and duration of OSA, severity of hypertension, and other factors that affect OSA severity and arterial injury as discussed in the Introduction.…”
Section: Discussionmentioning
confidence: 98%
“…Because obesity and insulin resistance tend to accompany OSA as comorbidities, it has been difficult to isolate the independent effect of OSA and its treatments on the development and consequences of hypertension. Several studies have postulated that increased sympathetic tone and endothelial dysfunction cause hypertension in OSA 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…To date few studies have evaluated the prevalence of MH in patients with OSA (ref. [15][16] ). Common finding of these studies was that the prevalence of MH is higher in OSA patients than the general population [15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] ). Common finding of these studies was that the prevalence of MH is higher in OSA patients than the general population [15][16] . Continuous positive airway pressure (CPAP) ventilator is considered to be the most effective treatment modality for obstructive sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several trials have indicated that treatment of OSAS can lead to reductions in hypertension and prehypertension. [3][4][5] The question then arises of how this is best accomplished. Diagnosis of obstructive sleep apnea (OSA) can be limited by availability, accessibility, and the cost of in-laboratory polysomnography: the gold standard for diagnosis.…”
mentioning
confidence: 99%